Pengaruh Financial Knowledge, Locus of Control dan Financial Attitude Terhadap Keputusan Penganggaran Modal (Studi Kasus di Dinas Koperasi dan UMKM Provinsi Bali) - gine das prena; Ni Made Listiyani Kartika (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2021)
Capital budgeting is a budget that includes a plan to acquire fixed assets in the form of land, buildings and items of capital equipment along with financial details. This budget can cover a considerable amount of time and the expenditure of funds includes large amounts. Budget receipts and expenditures require planning and control in order to achieve efficiency and effectiveness within government agencies so that capital budgeting decisions must be appropriate and in accordance with planned needs. In making a capital budgeting decision, it is measured by financial knowledge, self-control and financial attitudes possessed by employees in government agencies. The purpose of this study, the authors want to know about the effect of financial knowledge, self-control and financial attitudes on capital budgeting decisions. In this study, the location of the research was the Department of Cooperatives and SMEs in the Province of Bali with a sample of 35 respondents consisting of the Head of the Service and employees in each section. In determining the sample, the data collection method in this study is a purposive sampling method, which is based on predetermined criteria. The type of data used is quantitative data. The source of data in this study is primary data with questionnaires with data collection techniques using a Likers scale. The data analysis technique used is the classical assumption test, Descriptive Statistical Analysis, and multiple linear regression analysis. The results showed that financial knowledge, self-control and financial attitudes had a positive effect on capital budgeting decisions.